STUDI SISTEMATIS PEMANFAATAN MEDIA DIGITAL INTERAKTIF BERBASIS SCRATCH DALAM MENINGKATKAN LITERASI NUMERASI SISWA SEKOLAH DASAR - Tuti Alawiyah; Sardin (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Numeracy literacy is a fundamental competency that should be developed from the elementary education level. With the increasing integration of technology in teaching and learning processes, Scratch-based interactive digital media has been widely adopted as a tool to support numeracy learning. This study aims to systematically review the use of Scratch as an interactive digital medium for enhancing numeracy literacy among elementary school students. A Systematic Literature Review (SLR) was conducted following the PRISMA 2020 guidelines. Relevant studies were identified through searches of international and national databases using keywords related to Scratch, interactive digital media, numeracy literacy, and elementary education. Articles meeting the inclusion criteria were analyzed thematically to examine the characteristics of Scratch implementation, numeracy literacy components addressed, learning effectiveness, and supporting factors and implementation challenges. The results indicate that Scratch has a positive impact on students’ numeracy literacy, particularly in problem-solving abilities, understanding of number concepts, and mathematical representation skills. Moreover, the integration of Scratch with project-based learning and digital game-based approaches enhances student engagement and learning motivation. Nevertheless, challenges such as limited teachers’ digital competence and inadequate technological infrastructure remain significant barriers. These findings offer practical implications for educators and policymakers in optimizing the use of Scratch as an instructional medium for numeracy learning in elementary schools.